2021
DOI: 10.17759/chp.2021170314
|View full text |Cite
|
Sign up to set email alerts
|

Priming Future Cultural Identities in Self-Defining Future Projections: Findings of a Pilot Online Cross-Sectional Study

Abstract: A pilot cross-sectional online study attempts to clarify the role of implicit sociocultural attitudes in future thinking and tests a hypothesis that the implicit activation of Individualism / Collectivism concepts changes the content and other characteristics of self-relevant images of the future — self-defining future projections (SDFPs). The study performed in 2019-2020 involved 191 people, mean age — M = 36.9 (SD = 10.4) years. Group 1 underwent Individualism priming: 108 people (11.2% of males), mean age —… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 30 publications
2
3
1
Order By: Relevance
“…Consistent with the study comparing young and older adults’ SDFPs (Raffard et al, 2020), we found that participants extracted integrative meaning equally frequently whatever their age, with integrative statements featuring in around a third of SDFPs. This high level of integration is in accordance with previous studies (D’Argembeau et al, 2012; Tuchina et al, 2021). It suggests that in order to achieve their personal goals and find a sense of unity (McAdams, 2001), young, middle-aged and older adults all try to associate past and future self-relevant events in their life stories (Habermas & Köber, 2015) in the same way.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with the study comparing young and older adults’ SDFPs (Raffard et al, 2020), we found that participants extracted integrative meaning equally frequently whatever their age, with integrative statements featuring in around a third of SDFPs. This high level of integration is in accordance with previous studies (D’Argembeau et al, 2012; Tuchina et al, 2021). It suggests that in order to achieve their personal goals and find a sense of unity (McAdams, 2001), young, middle-aged and older adults all try to associate past and future self-relevant events in their life stories (Habermas & Köber, 2015) in the same way.…”
Section: Discussionsupporting
confidence: 93%
“…Compared to previous studies (D’Argembeau et al, 2012; Tuchina et al, 2021), the projections of our young participants were less oriented towards achievement in life but similar to Raffard and coworkers’ findings. A possible explanation for the difference between our adults and the Russian one's is that every participant collected just one SDFP in their study.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations